POTENTIAL AND REAL STUDENTS’ WILLINGNESS TO RESEARCH - Nina V. Bordovskaya; Svetlana N. Kostromina (Высшее образование в России)
This article is about the importance of students’ practical and potential willingness to research activity in view of the problem of student’s formation and development as a researcher at all levels of training at the university. The content of a term «research potential» as a most important precondition of scientific preparation success and research activity efficiency is specified. Studying of a student as a researcher is considered taking into account his scientific preparation and activity and also personal features that influence on success in research activity. Research potential of bachelors, master’s degree students, graduate students and young teachers is compared. The empirical basis of the article is the materials of studying research potential and extent of its realization by students and young teachers of different universities.